Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1007/s11916-002-0061-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidural lysis of adhesions and myeloscopy

Abstract: Chronic low back pain is one of the most common ailments in modern medicine, with as many as 79% of patients with acute pain continuing to suffer with chronic or recurrent low back pain 1 year after its onset. Lumbar epidural fibrosis and post-lumbar laminectomy syndrome are increasingly recognized as being responsible for persistent low back pain. Estimations show that approximately 5% to 40% of lumbar surgeries result in failed back surgery syndrome. Epidural adhesiolysis with myeloscopy is an interventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 78 publications
0
35
0
Order By: Relevance
“…In addition, initial clinical studies of spinal endoscopic adhesiolysis [23-29] and a preliminary report of a randomized controlled trial [30] showed improved clinical outcomes. However, a recent prospective, randomized, double-blind trial [31] comparing caudal epidural with targeted steroid placement on affected nerve roots during spinal endoscopy for chronic sciatica, concluded that targeted placement of steroid did not significantly reduce pain intensity and anxiety and depression compared with caudal epidural steroid injection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, initial clinical studies of spinal endoscopic adhesiolysis [23-29] and a preliminary report of a randomized controlled trial [30] showed improved clinical outcomes. However, a recent prospective, randomized, double-blind trial [31] comparing caudal epidural with targeted steroid placement on affected nerve roots during spinal endoscopy for chronic sciatica, concluded that targeted placement of steroid did not significantly reduce pain intensity and anxiety and depression compared with caudal epidural steroid injection.…”
Section: Introductionmentioning
confidence: 99%
“…Even though multiple authors have described various types of findings, including the identification of inflammation with an endoscope, neither the reliability nor the clinical utility of spinal endoscope as a diagnostic tool has been established [23-25,28,29]. Consequently, no attempt was made to evaluate the diagnostic utility of spinal endoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…If any surgery involves manipulation of the epidural space, then epidural fibrosis may be unavoidable. According to some studies, epidural fibrosis may be the reason or inductive factor for persistent pain in 20-36% of FBSS patients [50,51,[56][57][58] . If nerve roots' nutrition is damaged by perineural fibrosis due to cerebrospinal fluid circulation deficiency, then it may result in hypersensitivity of nerve roots [59] .…”
Section: Postoperative Factorsmentioning
confidence: 99%
“…There is no clinically proved surgical treatment for arachnoiditis, although myeloscopy with lysis of adhesions is currently under investigation. 3 Until more data are known, the treatment of patients with arachnoiditis is either nonsurgical, with Nerve root injections or blocks are useful both as a diagnostic and therapeutic modality.…”
Section: Neuropathic Injurymentioning
confidence: 99%